Perbandingan Pendapatan Usahatani Padi dan Cabe – Tembakau di Subak Gde Sukawati Gianyar - WIJAYANTI, PUTU UDAYANI; SUSRUSA, KETUT BUDI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
Comparison of Farming Income Rice and Chili – Tobacco in Subak Gde Sukawati Gianyar The sustainability or resilience of Subak appears to be under threat due to the rapid development of Bali tourism which has brought many changes in various aspects of Balinese life. Apart from the lack of interest among rural Balinese youth to work as farmers, another source of threat to the existence of subak is the rapid conversion of irrigated rice fields to uses other than agriculture. It seems that there are no definite figures regarding the area of ??rice fields that still exist today. However, sufficient information shows that in a period of 20 years around 15,000 ha of rice fields were lost because they were used for non-agricultural purposes. If the rice fields run out, the various benefits (multi-functional benefits) that can be achieved from the function of rice fields so far will disappear. The urgency of this research is to further understand decision making in situations of contradiction between the goal of maximizing income in one-crop farming and minimizing risk in farming with two crops on one paddy field. So it is deemed necessary to carry out this research regarding the sustainability of Subak in the future. The T test or T test is a statistical test used to test the truth or falsity of the null hypothesis which states that between two sample means taken randomly from the same population, there is no significant difference. From the results of the F table and T table, there are significant differences in the income from rice-chili and tobacco farming.